Forecasting the demand for electric vehicles in Singapore - Ong, Hui Ying (Nanyang Technological University, 2021)
The use of electric vehicles is rapidly increasing and is being encouraged in many countries in the world. Singapore is no exception, as numerous policies were introduced by the government in the recent Singapore Budget 2020 to encourage the use of electric vehicles in Singapore. The nation’s goal is to push out the use of internal combustion engine vehicles and have all vehicles to run on cleaner energy by 2040. However, the current electric vehicle population only stands at 0.24%. Thus, this project aims to analyse the extent of influence of factors – cost of owning an electric vehicle, availability of charging infrastructure, brand and variety of electric vehicles, charging time and driving range of electric vehicles, and environmental impacts of electric vehicles, on the demand for electric vehicles and thus carry out a forecast for the demand. The main mode of data collection is through a survey conducted online to gather responses of people’s attitudes towards electric vehicles and their knowledge of electric vehicle related government policies. The respective factors were further broken down into smaller areas to conduct a more detailed analysis. Respondents were asked to rank the various statements which represent the factors, on a scale of one to ten and provide their resulting decision with regards to purchasing or using an electric vehicle. The results collected will be modelled using the Logistic Regression Model to generate an equation relating demand for electric vehicles and the respective factors. Conclusion from the results was that the number of charging points available in both private and public housing estates has the highest positive influence, and the charging cost of electric vehicle has the lowest positive influence on the demand for electric vehicles. Recommendations and suggestions to increase the usage of electric vehicles in Singapore were provided based on the results obtained and were presented at the end of the report.